PECULIARITIES OF STATION ROTATION MODEL APPLICATION IN ONLINE LEARNING - Khalmatova, Ziyoda; BARIN, E. (Pedagogy and Psychology, 2025)
This study investigates the effectiveness of the blended learning model (online instruction station rotation model) that was implemented for Turkish as a foreign language A2 level students. The research took a mixed method approach, combining qualitative insights by ratio metrics in a quantitative manner. The data were gathered from a sample (n=16) of students who were listening and reading in the online instruction station rotation model. This research program was statistical, and it looked at students’ performances. Results showed that students performed better on true/false and matching tasks than fill-in-the-gap exercises. The research also found that spelling mistakes in dictation tasks occurred at a more frequent rate and indicated that students tended to code switch at the time of production, often reverting to their native language. The findings here provide important evidence of the characteristics of the challenges that learners face in this mode of instructional delivery. The study found that the students showed significant gains at stations for online instruction, in particular, when they worked on their own.